2018
DOI: 10.1002/chem.201802290
|View full text |Cite
|
Sign up to set email alerts
|

Steric and Electronic Factors Affecting the Conformation of Bimetallic CuI Complexes: Effect of the Aliphatic Spacer of Tetracoordinating Schiff‐Base Ligands

Abstract: A family of six homoleptic [Cu (L )] (ClO ) and six heteroleptic [Cu (L )(PPh ) ] (ClO ) bimetallic complexes, in which L are bis-Schiff base ligands with alkyl spacers of variable length (n=2-7 -CH -), were prepared to evaluate the role of the spacer on the formation of helicates or mesocates. In the homoleptic series, spectroscopic and theoretical studies indicate that preferences for a conformation are based on energetic parameters, mainly, the establishment of noncovalent interactions. The odd-even nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…39−41 This includes the dicopper(I) complexes [Cu 2 (L 3 ) 2 ] 2+ (a double helicate structure) 42 as well as the non-helical [(Ph 3 P)ICu(L 3 )CuI(PPh 3 )] 43 and [(Ph 3 P) 2 Cu(L 3 )Cu(PPh 3 ) 2 ] 2+ complexes. 44 Crystallographic analysis of [CuL 1 ](ClO 4 ) 2 and [CuL 2 ]-(ClO 4 ) 2 revealed them to be identical to their previously published structures, 15,18,19 and the crystal structures of [CuL 1 ](ClO 4 ) 2 , [CuL 2 ](ClO 4 ) 2 , and [CuL 3 ](ClO 4 ) 2 are compared in Figure 4. Despite their apparent similarity, they exhibit quite different coordination geometries and physical properties (Table 1) due to stereochemical changes at the ethylenediamine/diimine N-donors (N2 in Figure 3).…”
Section: ■ Results and Discussionsupporting
confidence: 55%
“…39−41 This includes the dicopper(I) complexes [Cu 2 (L 3 ) 2 ] 2+ (a double helicate structure) 42 as well as the non-helical [(Ph 3 P)ICu(L 3 )CuI(PPh 3 )] 43 and [(Ph 3 P) 2 Cu(L 3 )Cu(PPh 3 ) 2 ] 2+ complexes. 44 Crystallographic analysis of [CuL 1 ](ClO 4 ) 2 and [CuL 2 ]-(ClO 4 ) 2 revealed them to be identical to their previously published structures, 15,18,19 and the crystal structures of [CuL 1 ](ClO 4 ) 2 , [CuL 2 ](ClO 4 ) 2 , and [CuL 3 ](ClO 4 ) 2 are compared in Figure 4. Despite their apparent similarity, they exhibit quite different coordination geometries and physical properties (Table 1) due to stereochemical changes at the ethylenediamine/diimine N-donors (N2 in Figure 3).…”
Section: ■ Results and Discussionsupporting
confidence: 55%
“…In addition, there is a strong intramolecular ππ‐stacking interaction in the helicate, which arises from the stacking of two phenanthroline moieties from adjacent L 2 ligands, at a centroid‐centroid distance of 3.759 Å (Figure S2). We have previously reported that this type of non‐covalent interaction has a stabilizing effect on the structure of helicates, and consequently on the redox stability of the Cu(I) centers [47] …”
Section: Resultsmentioning
confidence: 99%
“…where L is the ligand. Di ́az 21 and Lemus 22 calculated the equilibrium constant (K) by NMR measurements, and the calculated value is about 10 −3 . The equilibrium makes the components and electrochemical properties rather complicated.…”
Section: ■ Introductionmentioning
confidence: 99%